Endoscopic mucosal resection or ablation for Barrett’s esophagus containing high grade dysplasia: agreement strongest among expert gastroenterologists - Canipe, Ashley; Slaughter, James; Yachimski, Patrick (Endoscopy International Open, 2014)
Background and study aims: Endoscopic mucosal resection (EMR) plays an important role in the staging of Barrett’s esophagus (BE) and the evaluation of high grade dysplasia (HGD). The study aim is to assess the interobserver agreement among gastroenterologists expert in BE endotherapy, gastroenterologists without specified expertise in BE endotherapy, and gastroenterology trainees in recommending EMR vs ablation for BE HGD lesions, and to assess the effect of a one-time educational intervention on the interobserver agreement among non-experts and trainees.Patients and methods: An electronic survey containing 30 still endoscopic images of BE HGD was sent to three groups of respondents: experts, non-experts, and trainees. Respondents were asked to select “Endoscopic Mucosal Resection” or “Ablation” as the most appropriate next step in management. Non-experts and trainees were then invited to repeat the survey following an educational intervention. The main outcome measure was interobserver agreement measured by Fleiss’ Kappa statistic and percent agreement.Results: In selecting between EMR and ablation, on the pre-intervention survey there was the highest amount of agreement among experts (kappa = 0.437), followed by agreement among trainees (kappa = 0.281), and non-experts (kappa = 0.107). Experts demonstrated significantly higher agreement compared to either trainees (P < 0.001) or non-experts (P < 0.001). On the post-intervention survey, interobserver agreement remained low among both trainees (kappa = 0.20) and non-experts (kappa = 0.14). Comparing the results of the surveys, there was no evidence that agreement differed for either trainees or non-experts.Conclusions: Future efforts are needed to enable endoscopist recognition of BE HGD lesions. Consensus guidelines alone are insufficient in directing preferred endoscopic management of BE HGD.